Cognitive and Emotional Dysfunction after Central Pontine Myelinolysis - Tatia M. C. Lee; Crystal C. Y. Cheung; Esther Y. Y. Lau; Amanda Mak; Leonard S. W. Li (Behavioural Neurology)
The case of a 67-year-old right-handed Chinese man with Central Pontine Myelinolysis [CPM] is described to illustrate the resulting cognitive and emotional disturbances. A comparison of the data in this report with that in published studies suggests that ethnicity does not seem to have much effect on the symptoms of CPM. Possible underlying neural-pathological mechanisms are discussed. This case further substantiates the speculation that the brainstem plays a role in higher cognitive processes and emotional regulation.